Government Securitizing Effort of Online Harmful Content in Indonesia - Putri, Treviliana Eka (Jurnal Komunikasi, 2023)
The emergence of the Internet and social media has altered theway individuals interact with each other.This has also led to the flourishmentof many user generated contents in many platforms, where platforms act asthe medium or environment for users’ posts and interactions. While thesedevelopment may contribute to bring space for ensuring citizens’ freedom ofspeech and expression, there also cases where the very same environmentis filled with ‘harmful’ contents such as fake news, hate speech, online fraud,etc. The government along with other related stakeholders in the field havethe responsibility to ensure such harmful contents do not manifests intooffline harms. In handling these issues, the government have often utilizelegal measures to apply sanctions for the platforms and or individual creatorsand restrict the spread of the contents. Using the securitization perspective,this study will look into Indonesian government current approach in tacklingthe online harmful content. This study argue that the government has put theissue into a higher level, putting it into the national security agenda, in whichresulting in some extraordinary measure being applied in several instances.Nonetheless, this study suggests that it is of importance for the governmentand all related stakeholders to de-securitize the issue, putting it into theeveryday discussion and politics, while ensuring the protection of citizens’rights.